Reversible Watermark Using an Accurate Predictor and Sorter Based on Payload Balancing - Kang, Sang‐ug; Hwang, Hee Joon; Kim, Hyoung Joong (ETRI journal, 2012)
A series of reversible watermarking technologies have been proposed to increase embedding capacity and the quality of the watermarked image simultaneously. The major skills include difference expansion, histogram shifting, and optimizing embedding order. In this paper, an accurate predictor is proposed to enhance the difference expansion. An efficient sorter is also suggested to find a more desirable embedding order. The payload is differently distributed into two sub‐images, split like a chessboard pattern, for better watermarked image quality. Simulation results of the accurate prediction and sorter based on the payload balancing method yield generally better performance over previous methods. The gap is wide, in particular, in low payload for natural images. The peak signal‐to‐noise ratio improvement is around 2 dB in low payload ranges.